2014
DOI: 10.1177/1403494814538559
|View full text |Cite
|
Sign up to set email alerts
|

Sickness benefit cuts mainly affect blue-collar workers

Abstract: The cuts in sickness benefits had a major impact on the use of sickness absence by blue-collar employees with low salaries. This indicates that lower income was a major factor hindering the use of sick leave as these employees are most vulnerable to the loss of income.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…As shown in Online Appendix Table , most studies evaluated the immediate impact of sick leave and medical leave policies on policy uptake and personal absences from work. This research generally showed that personal sick leave was responsive to changes in policy, with laws that restricted eligibility or benefits typically associated with reductions in mostly short‐term leave‐taking behavior, and vice versa …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As shown in Online Appendix Table , most studies evaluated the immediate impact of sick leave and medical leave policies on policy uptake and personal absences from work. This research generally showed that personal sick leave was responsive to changes in policy, with laws that restricted eligibility or benefits typically associated with reductions in mostly short‐term leave‐taking behavior, and vice versa …”
Section: Resultsmentioning
confidence: 95%
“…The simplest strategy for addressing unmeasured differences between countries that might affect whether or not a country adopts a particular policy, as well as the outcome of interest, is to compare outcomes before and after the implementation of a policy within a treated country. This before‐and‐after or pre‐post design was commonly used to evaluate leave policies . The validity of the pre‐post comparison depends on the assumption that pre‐reform outcome trends are a valid substitute for trends in the post‐policy period had the policy not been implemented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivation to return to work and at the same time the effects of cardiac rehabilitation may be different according to the type of work. Some authors proved that lower income may hinder the use of sick leave by blue-collar employees as these employees are most vulnerable to the loss of income [11]. This factor, but also social and sickness benefits from the illness, can bias the effects of HCR.…”
Section: Discussionmentioning
confidence: 99%
“…tasks, equipment/tools, and organization), organization safety culture and social context (i.e. labour market, social security systems, national health systems) [5,8,10,[12][13][14]. Several workplace interventions have been implemented in different working populations, including nursing staff, to prevent and reduce MSP and to promote an early return to work after sickness absence, and multifaceted interventions have shown to be more effective than those based on a single component [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%